Research of market value of multistory housing in Vilnius - Raslanas, Saulius (Technological and Economic Development of Economy, 2004)
Over the recent years the market of multistory housing in Vilnius has developed intensively. For several years the VGTU Property Valuation Science Centre is doing the research into the market of multistory housing of Vilnius applying the regressive‐correlative analysis. The location (neighborhood), a house type, the year of construction and the condition of the flat have the biggest influence on flat pricing. During the analysis process of selling prices in separate neighborhoods of Vilnius similar results of variations in price curves are received. The dynamics of flat pricing in Vilnius over the last 7 years indicates the price cycle which lasted for 6 years ‐ from 1999 to 2004. During the first two years (till 2001) prices were decreasing. Later, the increase in pricing began and is lasting til now. During the year 2004 an average market value of 1 m2 of flats in residential zoning districts of Vilnius (2366 Lt) has risen by 28% in comparison to 2003 value (1705 Lt). This year the value reached the highest value level of the year 1999 and has exceeded it by 12%. If compared to the lowest value level in 2001, an average market value of 1 m2 has increased by 42% in 2004. With this periodic dynamics of housing pricing it is very dangerous to valuate it according to the market value in the case of mortgage when banks assign loans. The valuation of real estate in the case of lending must be based on sustainable value the setting of which requires mathematic‐statistical research. Article in Lithuanian. Vilniaus miesto daugiaaukščio būsto rinkos vertės tyrimai First Published Online: 21 Oct 2010